The wall paintings of the church of San Pablo de Cacha (Canchis, Peru) - Cohen Suárez, Ananda (2011)
Recently discovered by a team of restorers, the mural paintings of the Church of San Pablo de Cacha in the Canchis Province of southern Peru have received little scholarly attention. This article provides the first iconographic study of the Church's rich murals, examining them in light of their broader historicaland cultural relevance. The paintings were produced in two distinct phases: the first phase corresponds to the early seventeenth century and the second phase was carried out in the late eighteenth century. This study considers the radically different social contexts within which these images were produced andthe distinct meanings that they may have transmitted to local congregations during these two critical moments in colonial Andean history.